2022
DOI: 10.1007/s11109-022-09776-4
|View full text |Cite
|
Sign up to set email alerts
|

Voters Use Campaign Finance Transparency and Compliance Information

Abstract: Campaign finance compliance and transparency reveal important non-policy attributes that voters care about. Using vignette and conjoint survey experiments, I show that voters in primary elections incorporate transparency and compliance considerations into candidate selection. This effect persists even where the candidate shares the respondents’ preferred policy positions. The findings bring campaign finance transparency and compliance into the scholarly conversation about candidate valence. They also have impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Carson 2015), and concentrating solely on advertising. This would fit with other works on dark money (Oklobdzija 2019 andWood andSpencer 2016), who found evidence that avoiding cross pressures from one's social context may be a powerful motivator for opting to give in secret. Fairly innocuous party building and campaign activities would incur less backlash against a donor than a highly charged political ad or one that stakes out a controversial issue position.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Carson 2015), and concentrating solely on advertising. This would fit with other works on dark money (Oklobdzija 2019 andWood andSpencer 2016), who found evidence that avoiding cross pressures from one's social context may be a powerful motivator for opting to give in secret. Fairly innocuous party building and campaign activities would incur less backlash against a donor than a highly charged political ad or one that stakes out a controversial issue position.…”
Section: Discussionsupporting
confidence: 83%
“…As Wood (2022) demonstrates, voters use information about campaign finance transparency to inform their votes in candidate races, punishing candidates who rely on nondisclosing organizations for support. Further, Dowling and Wichowsky (2015) find that voters discount the advertising of outside groups when they learn about the group’s financiers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far we have focused on a stark comparison of campaign finance institutions: mandatory disclosure where the Donor's identity is always attached to advertising and no disclosure where the Donor-funded ads never reveal source information. While doing so allowed us to present the key mechanisms most clearly, in reality many donors that could use dark money voluntarily choose to disclose, or "over-comply" with campaign finance transparency principles (Wood 2022). 15 As Wood (2018, 16) notes: "In any race in which dark money is present, so, too, is the opportunity to select into a disclosure condition."…”
Section: Extensionsmentioning
confidence: 99%
“…Empirical research has shown that financial information cues can affect assessments of candidates Wichowsky 2013, 2015;Dowling and Miller 2016;Prat, Puglisi and Snyder Jr. 2010;Rhodes et al 2019), including ideological information (Oklobdzija 2019), assessments of policy initiatives (Boudreau and MacKenzie 2021), perceptions of political corruption (Spencer and Theodoridis 2020), vote choice (Robinson 2022), 6 news coverage of money in politics (La Raja 2007), and the efficacy of political advertising (Brooks and Murov 2012;Ridout, Franz and Fowler 2015;Weber, Dunaway and Johnson 2012). In addition, recent research shows that voters respond to both campaign finance information and cues about compliance with campaign finance transparency principles (Wood 2022;Wood and Grose 2020). The general takeaway from this literature is that campaign finance disclosure can affect perceptions of candidates and voter behavior through voter learning that occurs when donor information is provided.…”
mentioning
confidence: 99%